BENTUK DAN PROSES PENCIPTAAN TARI BETARI AMONG KITRI - Sari, Gigis Setia Puspita (Greget : Jurnal Kreativitas dan Studi Tari, 2024)
The basic idea of ​​the research entitled "The Form and Process of Creating the Betari Among Kitri Dance", which is based on the story of the fertility religious myth Nyai Sekar Sari, aims to provide a descriptive explanation of the form and process of creating the Betari Among Kitri Dance.This research uses a descriptive field research method that emphasizes data collection through observation, interviews, and literature studies, collecting data through a Participation Action Research (PAR) approach involving researchers as dancers and choreographers using a field approach and then packaged descriptively.This research uses the theory of Y. Sumandiyo Hadi, 2003 which is used to discuss the form of the Betari Among Kitri Dance work and the theory of Alma M. Hawkins which is used to solve problems regarding the process of creating the Betari Among Kitri Dance work. In the form of exploring the elements in the Betari Among Kitri Dance work, namely: (1) theme (2) dance title (3) synopsis (4) type of dance (5) dance description (6) dance movements (7) dance space (8) floor pattern (9) dance accompaniment / music (10) dancers (number and gender) (11) make-up and dance costumes (12) lighting and stage setting (13) mode of presentation. The process of creating this work goes through the preparation, design and composition stages, including the exploration, improvisation and composition stages. The results of this research can describe the form and process of creating the Betari Among Kitri dance work.